Graphemes Sharing Phonetic Features Tend to Induce Similar Synesthetic Colors - Kang, Mi-Jeong; Kim, Yeseul; Shin, Ji-Young; Kim, Chai-Youn (Frontiers in Psychology, 2017)
Individuals with grapheme-color synesthesia experience idiosyncratic colors when viewing achromatic letters or digits. Despite large individual differences in grapheme-color association, synesthetes tend to associate graphemes sharing a perceptual feature with similar synesthetic colors. Sound has been suggested as one such feature. In the present study, we investigated whether graphemes of which representative phonemes have similar phonetic features tend to be associated with analogous synesthetic colors. We tested five Korean multilingual synesthetes on a color-matching task using graphemes from Korean, English, and Japanese orthography. We then compared the similarity of synesthetic colors induced by those characters sharing a phonetic feature. Results showed that graphemes associated with the same phonetic feature tend to induce synesthetic color in both within- and cross-script analyses. Moreover, this tendency was consistent for graphemes that are not transliterable into each other as well as graphemes that are. These results suggest that it is the perceptual — i.e., phonetic — properties associated with graphemes, not just conceptual associations such as transliteration, that determine synesthetic color.